Saccadic suppression in schizophrenia - Rebekka Lencer (Nature Portfolio, 2021)
Abstract About 40% of schizophrenia patients report discrete visual disturbances which could occur if saccadic suppression, the decrease of visual sensitivity around saccade onset, is impaired. Two mechanisms contribute to saccadic suppression: efference copy processing and backwards masking. Both are reportedly altered in schizophrenia. However, saccadic suppression has not been investigated in schizophrenia. 17 schizophrenia patients and 18 healthy controls performed a saccadic suppression task using a Gabor stimulus with individually adjusted contrast, which was presented within an interval 300 ms around saccade onset. Visual disturbance scores were higher in patients than controls, but saccadic suppression strength and time course were similar in both groups with lower saccadic suppression rates being similarly related to smaller saccade amplitudes. Saccade amplitudes in the saccadic suppression task were reduced in patients, in contrast to unaltered amplitudes during a saccade control task. Notably, smaller saccade amplitudes were related to higher visual disturbances scores in patients. Saccadic suppression performance was unrelated to symptom expression and antipsychotic medication. Unaltered saccadic suppression in patients suggests sufficiently intact efference copy processing and backward masking as required for this task. Instead, visual disturbances in patients may be related to restricted saccadic amplitudes arising from cognitive load while completing a task.